2012
DOI: 10.1017/s0029665112003370
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of growing-up milks to the diets of Irish children aged 12–36 months

Abstract: Over the last decade, growing-up milks have become available commercially in Ireland for children aged 12-36 months to complement a balanced diet and to help reduce the risk of nutrient inadequacies. The aim of this paper is estimate the intake and contribution to the energy and nutrient intakes of growing-up milks in Irish children aged 12-36 months. Analyses were based on data from the National Pre-School Nutrition Survey (2010-2011), a nationally representative survey of food consumption in 1-4 year old Iri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the NPNS (2010–11), GUM were reported to be consumed by 25% of children aged 12–24 months in Ireland where whole cow's milk was most widely consumed (88% consumers) and other milks consumed were reduced fat cow's milk (14%), breast milk (7%), follow-on formula (6%), and soya/rice milk alternatives (2%) ( 4 ). In that study, consumption of GUM was less common in children aged 25–36 months (14% consumers) ( 26 ).…”
Section: Discussionmentioning
confidence: 83%
“…In the NPNS (2010–11), GUM were reported to be consumed by 25% of children aged 12–24 months in Ireland where whole cow's milk was most widely consumed (88% consumers) and other milks consumed were reduced fat cow's milk (14%), breast milk (7%), follow-on formula (6%), and soya/rice milk alternatives (2%) ( 4 ). In that study, consumption of GUM was less common in children aged 25–36 months (14% consumers) ( 26 ).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, many studies have also reported that the consumption of vitamin D fortified milk/GUM effectively increases dietary intakes and serum 25(OH)D concentrations in many population groups, including young children . It is important to note that only a small proportion (20%) of 12–36‐month‐old Irish children consume GUM and, despite milk being an important food group in the diets of young children (consumed by 99% of 1–4‐year‐old children) , few commercially available cows’ milks are currently fortified with vitamin D in Ireland. We found that fortifying CM with 2 μg of vitamin D/100 mL would decrease the prevalence of inadequacy from 97% at baseline to <70% for 1‐ and 2‐year‐old children and <80% for 3‐ and 4‐year‐old children.…”
Section: Discussionmentioning
confidence: 99%